2011
DOI: 10.1007/s00467-011-1779-z
|View full text |Cite
|
Sign up to set email alerts
|

Hemodiafiltration: the addition of convective flow to hemodialysis

Abstract: Hemodiafiltration (HDF) combines both hemofiltration (HF) and hemodialysis in the same procedure. It was initially performed in adults in 1977, and later used in children in the early 1980s. The use of HDF allows a determined convective dialysis dose to be combined with the conventional urea dialysis dose. The dialysis session is better tolerated as a result of the effects of hemofiltration. On-line HDF, i.e., substitution fluid prepared from ultrafiltration of the ultrapure dialysate, can be performed safely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Thus, technical improvements in HD have primarily focused on the development of biocompatible antioxidant dialyzer membranes45, and the modification of dialysates67. Also, efforts have been done to increase the efficiency and safety of HD using convective therapies8, ultrapure dialysate9 and intelligent therapy control with advanced dialysis machines10. Current renal substitution therapy with HD or home-based peritoneal dialysis (PD) has been the only successful long-term ex vivo organ substitution therapy for sustaining life11, while technical advances directed at improving clinical outcomes in both HD and PD have been limited.…”
mentioning
confidence: 99%
“…Thus, technical improvements in HD have primarily focused on the development of biocompatible antioxidant dialyzer membranes45, and the modification of dialysates67. Also, efforts have been done to increase the efficiency and safety of HD using convective therapies8, ultrapure dialysate9 and intelligent therapy control with advanced dialysis machines10. Current renal substitution therapy with HD or home-based peritoneal dialysis (PD) has been the only successful long-term ex vivo organ substitution therapy for sustaining life11, while technical advances directed at improving clinical outcomes in both HD and PD have been limited.…”
mentioning
confidence: 99%
“…To achieve euvolaemia many nephrologists prescribe high ultrafiltration rates [17], especially if the patient appears to tolerate it [3,8]. A patient's tolerance to a higher ultrafiltration rate depends on many factors, including maintaining normal haemoglobin levels, the use of bicarbonate dialysate buffe r, h i g h e r d i a l y s a t e s o d i u m c o n c e n t r a t i o n [ 5 ] , haemodiafiltration technology [18], ultrafiltration or sodium profiling, lowering dialysate temperature and on-line blood volume monitoring [9,10], and has dramatically improved over the last decades [6]. Nonetheless, even a well-tolerated high ultrafiltration rate, such as >1.24 % body weight loss per hour in adults, is associated with greater mortality [19].…”
Section: Managing Idwg: Safely Achieving the Desired Ultrafiltrationmentioning
confidence: 99%
“…HDF is the addition of a determined convective volume to HD [18], thereby allowing for blood purification combining diffusive mass transport of small uraemic toxins and convective mass transfer of larger middle-molecular weight uraemic toxins. The total convective volume achieved over a HDF session is the sum of the prescribed weight loss and the predetermined ultrafiltration flow of blood, with ultrafiltration replaced by an equal volume of substitution fluid in order to achieve a large convective volume.…”
Section: Managing Idwg: Safely Achieving the Desired Ultrafiltrationmentioning
confidence: 99%
“…Based on their clinical experience, Fischbach et al reported that high-efficiency HDF also had beneficial effects in the pediatric setting [44]. Thumfart et al combined NIHD with HDF (NHDF) in a prospective cross-over study [45] and found that serum phosphate concentration was significantly reduced in both intensive dialysis modalities, with NIHD lowering the phosphate concentration by 0.43 mg/dl and NHDF lowering it by 0.5 mg/dl despite the discontinuation of phosphate binders [45].…”
Section: Intensified Dialysis Programs For Children and Adolescentsmentioning
confidence: 99%